2021
DOI: 10.3390/ijms22041843
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors VEGF-A165 and FGF-2 as Multifunctional Biomolecules Governing Cell Adhesion and Proliferation

Abstract: Vascular endothelial growth factor-A165 (VEGF-A165) and fibroblast growth factor-2 (FGF-2) are currently used for the functionalization of biomaterials designed for tissue engineering. We have developed a new simple method for heterologous expression and purification of VEGF-A165 and FGF-2 in the yeast expression system of Pichia pastoris. The biological activity of the growth factors was assessed in cultures of human and porcine adipose tissue-derived stem cells (ADSCs) and human umbilical vein endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Cell adhesion is the predominant process during the first day of cell culture. In addition, FGF-2 has been observed to inhibit adhesion of ECs [ 65 ]. This effect may contribute to comparable cell indexes of the Hep-containing and pure Alg samples, although the Alg microbeads released a lower FGF-2 amount.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell adhesion is the predominant process during the first day of cell culture. In addition, FGF-2 has been observed to inhibit adhesion of ECs [ 65 ]. This effect may contribute to comparable cell indexes of the Hep-containing and pure Alg samples, although the Alg microbeads released a lower FGF-2 amount.…”
Section: Resultsmentioning
confidence: 99%
“…However, FGF-2 evinced an inhibitory effect on HUVEC adhesion but a strong enhancement of cell proliferation. In contrast, VEGF affected cell proliferation only moderately, with no negative effect on HUVEC adhesion [ 65 ]. These data correlate with our findings on proliferation in a nutrient-deprived culture medium, where FGF-2 in the eluates exhibited a stronger effect on HUVEC proliferation than VEGF, and the cells exposed to FGF-2 probably developed more cell–cell contacts that prevented the cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the data indicated that oxostephanine decreased the production of VEGF-A, HGF and FGF-2, which functions in the proliferation, migration and tube formation processes (48)(49)(50)(51), by both hUVEcs and hFBs. Notably, in the present study, in hUVEcs, the mRNA expression of VEGF-A in cells treated with oxostephanine was not considerably altered; however, the expression of FGF-2 was significantly decreased compared to the control.…”
Section: Discussionmentioning
confidence: 96%
“…No. 89050205) seeded in soft foams scaffolds, incubated in 24 or 96-well plates was measured with a resazurin assay according to Sedlář, et al [4]. ASCs were isolated from lipoaspirates and characterized according earlier study [5].…”
Section: Metabolic Aktivity Assaymentioning
confidence: 99%